Correction: Selenium borohydride reaction as a versatile platform for the straightforward preparation of selenide-containing topological polymers. Issue 25 (15th June 2017) - Ding, Chunlai; Fan, Caiwei; Pan, Xiangqiang; Zhang, Zhengbiao; Zhu, Jian; Zhu, Xiulin
Abstract : Correction for 'Selenium borohydride reaction as a versatile platform for the straightforward preparation of selenide-containing topological polymers' by Chunlai Ding et al., Polym. Chem., 2017, DOI: 10.1039/c7py00676d.